Advanced cathode materials in dual‐ion batteries: Progress and prospect. Issue 4 (26th August 2021) - Li, Wen‐Hao; Wu, Xing‐Long
Abstract: Dual‐ion batteries (DIBs) utilize the working mechanism, that is, anions and cations participate in electrochemical reactions on the cathode and anode materials to achieve energy storage simultaneously. The high potential of anions de‐/intercalation endows DIBs with high energy density. However, the relatively low specific capacity and poor interface stability limit the further development of DIBs. Therefore, improving the performance of cathode materials has become the key to promoting the practical application of DIBs. In this review, a variety of DIBs cathode materials are classified in detail and their energy storage mechanism and typical characteristics are comprehensively summarized. Finally, the rules and corresponding strategies which should be followed in the design of high energy cathode materials are proposed, and the potential development direction of DIBs in the future is summarized. Abstract : Dual‐ion batteries (DIBs) have received extensive attentions from the research community due to its high specific energy, high safety, and low cost. However, the low capacity and poor stability of cathode materials have restricted their development. In this review, the history of DIBs cathode materials was sorted out and suggestions and prospects were put forward for the design of high‐performance cathode materials in the future.